Doctors’ Perceptions towards Domestic and Multinational Pharmaceutical Products: An Investigation from Developing Country - Ahmed, Jashim Uddin; Chowdhury, Md. Humayun Kabir; Synthia, Ishrat Jahan; Sultana, Ishrat (UI Scholars Hub, 2021)
This exploratory study focuses on doctors’ perception towards domestic and multinational pharmaceutical products. Doctors can heavily influence drug purchase decisions by performing the roles of users (sometimes), influencer, gatekeepers and deciders, while patients perform the role of buyers and users. The difference in perception was measured in terms of products, brand image and pricing. Data were collected from a sample of 15 doctors (n=15) using a questionnaire comprised of 12 questions measured in Likert scales. The study reveals that brand image is the most influential factor for price of medicines and brand image is highly related to quality and the level of promotion for the underlying product. Furthermore, doctors perceive multinational products to be different and better than domestic products due to their stronger brand image. This study highlights that doctors’ preferences are not fully unbiased and can be influenced by pharmaceutical companies. Due to its exploratory nature, findings might need to be validated in a further study with a larger sample.